Comparing is a matter of method: teaching and compared knowledge turnout at the colombian academy (2010)
A field of academic-disciplinary study is defined by the problems and subjects it deals with, the main theories regarded as reliable and scientific, and the methodologies used. In political science, compared politics is one of the areas with the most significant methodological (how to draw a comparison) and substantial (what to compare) developments. This article introduces a consideration on compared politics in Colombia, searching for answers to the following questions: has the Colombian academy incorporated compared politics to teaching and research? And, if so, in which way? The article focuses on the explicitly comparative approaches placing teaching and academic production as elements of reflection. An analysis of curricula regarding courses with comparative denominations is undertaken. From the generation of knowledge based on the compared methodology, articles published in magazines specialized in Colombian political matters are analyzed. On the basis of these considerations, a balance and assessment of teaching and specialized works is accomplished.